Impact of Preventive and Therapeutic Zinc Supplements on Citrulline Concentration and the kynurenine: tryptophan Ratio Among Lao Children: A Randomized Controlled Trial (OR07-02-19). (13th June 2019) - Wessells, K Ryan; Hinnouho, Guy-Marino; Barffour, Maxwell; Sayasone, Somphou; Arnold, Charles; Kounnavong, Sengchanh; Brown, Kenneth; Hess, Sonja
Abstract: Objectives: To investigate the impact of different forms of zinc supplementation on plasma citrulline (CIT), kynurenine (KYN) and tryptophan (TRP) concentrations and the kynurenine: tryptophan ratio (KTR), considered as markers of intestinal function and systemic inflammatory response, among young Lao children. Methods: In a randomized controlled double-blind trial, 3407 children aged 6–23 mo were randomized into one of four groups and followed for ∼36 weeks: daily preventive zinc dispersible tablet (7 mg zinc; PZ), daily multiple micronutrient powder (10 mg zinc, 6 mg iron and 13 other micronutrients; MNP), therapeutic zinc supplements for the treatment of diarrhea (20 mg/d for 10 days with each diarrhea episode; TZ), or daily placebo powder (Control). Plasma samples at baseline and endline for 359 children participating in the parent trial were analyzed at the NIH West Coast Metabolomics Center (UC Davis); plasma CIT, KYN and TRP concentrations were determined by hydrophilic interaction chromatography (HILIC) quadrupole time of flight mass spectrometer (QTOF) tandem mass spectrometry (MS/MS). Linear regression models were used to assess the treatment effect, controlling for baseline value, child age and district. Results: The parent trial found no overall group-wise effects on linear growth or diarrhea outcomes. In the subgroup included in the present analyses, mean age at enrollment was 16.0 ± 4.9 mo, 37% were stunted and 83% were zinc deficient. At baseline, mean plasma CIT, KYN and TRP concentrations were 24.6 ± 5.4 µM, 3.27 ± 0.83 µM and 72.3 ± 12.9 µM, respectively; the mean KT ratio was 0.046 ± 0.013. 5% of children had low CIT (< 17 µM) and no children had low TRP (< 35 µM). At endline, there were no differences among intervention groups in mean plasma CIT (25.0–26.6 µM, P = 0.287), KYN (2.96–3.11 µM, P = 0.115), TRP (66.1–70.0 µM, P = 0.151) or the KTR (0.046–0.047, P = 0.981). Conclusions: In this population, PZ, MNP and TZ had no overall effect on plasma concentrations of CIT, KYN, TRP and the KTR. We plan to further explore if these markers of intestinal function were predictive of subsequent linear growth, or modified the growth response to supplementation. Funding Sources: The Bill & Melinda Gates Foundation, Nutrition International and the Mathile Institute for the Advancement of Human Nutrition.